Should Inequality Factor into Central Banks' Decisions? - Hansen, Niels-Jakob (IMF Working Papers; Working Paper, 2020)
Inequality is increasingly a concern. Fiscal and structural policies are well-understood mitigators. However, less is known about the potential role of monetary policy. This paper investigates how inequality matters for monetary policy within a tractable Two-Agent New Keynesian model that captures important dimensions of inequality. We find some support for making inequality an explicit target for monetary policy, particularly if central banks follow standard Taylor rules.